1996
DOI: 10.1007/bf00785770
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms over the course of HIV infection before AIDS

Abstract: The objective of this study was to describe the prevalence and course of depressive symptoms before AIDS in HIV-infected homosexual men. A descriptive and comparative analysis of data from HIV-infected and -uninfected homosexual men in the Multicenter AIDS Cohort Study was performed. The Center for Epidemiologic Studies Depression Scale (CES-D) was the primary measure of depressive symptoms. The prevalence of depressive symptoms and CES-D caseness estimates in the AIDS-free HIV-infected homosexual men were sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 38 publications
0
44
3
Order By: Relevance
“…Cross-sectional data also prevented us from measuring changes in depressive symptoms, although other researchers have reported that mood tends to remain stable among HIV-infected patients, even with increased HIV illness severity. 2,3,16 Second, while we did not find a significant problem with collinearity, such findings comparing the clinical significance of depressive and HIV or other physical symptoms need to be interpreted with caution because of the potential for overlap between depressive and physical symptoms. Although we found no significant interaction between depressive symptoms and HIV symptom count, our power to detect such interactions was low.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Cross-sectional data also prevented us from measuring changes in depressive symptoms, although other researchers have reported that mood tends to remain stable among HIV-infected patients, even with increased HIV illness severity. 2,3,16 Second, while we did not find a significant problem with collinearity, such findings comparing the clinical significance of depressive and HIV or other physical symptoms need to be interpreted with caution because of the potential for overlap between depressive and physical symptoms. Although we found no significant interaction between depressive symptoms and HIV symptom count, our power to detect such interactions was low.…”
Section: Discussionmentioning
confidence: 66%
“…21 The CES-D has been widely used in studies of the relationship between HIV and depression. 2,3,13,14,22 We used the CES-D 10-item survey rather than a more comprehensive instrument such as the Diagnostic Interview Schedule in order to minimize respondent burden. Patients screened positive for significant depressive symptoms if they obtained a standard cut point of 10 or more out of a possible 30 points.…”
Section: Measures Depressive Symptomsmentioning
confidence: 99%
“…Findings of change in, or persistence of, psychiatric morbidity in HIV/AIDS have been mixed [3][4][5][6][7][8][9][10][11]. While some studies have found a modest increase in anxiety and depression on follow-up [3][4][5], other studies have found diagnostic status to be stable over time [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the severity of depression correlates with the HIV disease progression [21,22]. Furthermore, depression was associated with lower medication adherence and higher mortality [23][24][25].…”
Section: What Is Known About Depression and Hiv?mentioning
confidence: 99%